Outbreaks of foot and mouth disease in Egypt: Molecular epidemiology, evolution and cardiac biomarkers prognostic significance - Sobhy, Nader M. (Int J Vet Sci Med, 2018)
Foot and mouth disease virus (FMDV) was isolated from sloughed tongue epithelium of Egyptian cattle presenting with mouth lesions and ropy salivation in two Egyptian governorates (El-Fayoum and Dakahlia). The virus was isolated in Madin-Darby bovine kidney (MDBK) cells and identified by reverse transcription-polymerase chain reaction (RT-PCR). The complete genome was obtained by next generation sequencing. The strains isolated from El-Fayoum and Dakahlia were serotype A and O, respectively and both isolates had identity with the previously reported Egyptian strains. This study reports successive outbreaks of FMDV that occurred in Egypt during 2015–2016 and describes the dynamics of two outbreaks in addition to the use of cardiac biomarkers in the diagnosis of FMD-related myocarditis in calves and its clinical relevance. Serum cardiac troponin1 (cTn I) and creatinine kinase myocardial band (CK-MB) were measured. Mean serum cardiac troponin1 (cTn I) showed significant increase (P < 0.001) in FMDV-infected calves. The increase in fatal and recovered cases was (2.794 ± 0.502 ng/mL) and (1.196 ± 0.443 ng/mL), respectively, compared to the healthy control cases (0.014 ± 0.002 ng/mL). Thus, the serum cTn-I successfully diagnosed FMD-associated myocarditis in calves but not prognostic for the fatal cases. The FMDV sequences described in this study should further help in studying FMDV endemicity in Egypt, tracking the source of infection, selection of control strategies and vaccine updates. The study also determines the clinical relevance of cardiac biomarkers in diagnosis of FMDV-related myocarditis in infected calves.